1995
DOI: 10.1152/ajpregu.1995.269.5.r1204
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin-like growth factor-I (IGF-I) and IGF-binding proteins by tumor necrosis factor

Abstract: The purpose of the present study was to determine 1) whether exogenous administration of tumor necrosis factor-alpha (TNF-alpha) alters insulin-like growth factor-I (IGF-I) and IGF-binding proteins (BPs) and 2) whether the enhanced endogenous production of TNF mediates the lipopolysaccharide (LPS)-induced changes in the IGF system. The overnight infusion of murine TNF-alpha reduced circulating concentrations of both growth hormone (GH) and IGF-I in fasted rats. Furthermore, TNF-alpha decreased IGF-I content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
116
3
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(133 citation statements)
references
References 0 publications
8
116
3
6
Order By: Relevance
“…After surgery, all rats were housed in individual cages with no food but with water ad libitum. We have previously reported that this experimental protocol elevates the blood TNF-␣ concentration to ϳ500 pg/ml (12). Comparable TNF-␣ values are observed in a number of inflammatory conditions, including sepsis, neoplastic disease, burn injury, and hepatic ischemia-reperfusion injury (6,7,9,11), but levels are markedly lower than those seen in rats injected with nonlethal doses of endotoxin (18).…”
Section: Methodsmentioning
confidence: 81%
See 4 more Smart Citations
“…After surgery, all rats were housed in individual cages with no food but with water ad libitum. We have previously reported that this experimental protocol elevates the blood TNF-␣ concentration to ϳ500 pg/ml (12). Comparable TNF-␣ values are observed in a number of inflammatory conditions, including sepsis, neoplastic disease, burn injury, and hepatic ischemia-reperfusion injury (6,7,9,11), but levels are markedly lower than those seen in rats injected with nonlethal doses of endotoxin (18).…”
Section: Methodsmentioning
confidence: 81%
“…Comparable TNF-␣ values are observed in a number of inflammatory conditions, including sepsis, neoplastic disease, burn injury, and hepatic ischemia-reperfusion injury (6,7,9,11), but levels are markedly lower than those seen in rats injected with nonlethal doses of endotoxin (18). In addition, this dose of TNF-␣ also produces peripheral insulin resistance (29) and decreases the IGF-I content in blood and muscle (12).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations